MgO-Based Fabry-Perot Vibration Sensor with a Fiber-Optic Collimator for High-Temperature Environments - Jiacheng Tu; Qirui Zhao; Jiantao Hu; Yuhao Huang; Haiyang Wang; Jia Liu; Pinggang Jia (Photonics)
In this paper, a MgO-based high-temperature Fabry-Perot (F-P) vibration sensor with a fiber-optic collimator is proposed and experimentally demonstrated at 1000 °C. The sensor is composed of a sensing unit and a fiber-optic collimator. The F-P cavity is formed by the upper surface of the inertial mass block and the countersunk hole of the cover layer. The length of the F-P cavity changes with external vibrations. The sensing unit is prepared by wet etching technology and three-layer direct bonding technology, which ensure its stability and reliability in high-temperature environments. The experimental results indicate that the sensor can operate stably within a range from room temperature up to 1000 °C. The sensitivity and non-linearity of the sensor at 1000 °C are 1.3224 nm/g and 3.8%, respectively. Furthermore, the sensor operates at frequencies of up to 4 kHz while remaining unaffected by lateral vibration signals. The high-temperature F-P vibration sensor can effectively deal with the fiber damage in extreme environments and exhibits considerable potential for widespread applications.